A deep dive into the development of complex generics: A comprehensive review - Amatha Sreedevi, Prashant B. Musmade, Krishnamurthy Bhat, Sreedhar Dharmagadda, Manthan D. Janodia, Bhavana B. Bhat, Virendra S. Ligade (Journal of Applied Pharmaceutical Science, 2024)
In recent years, complex generics a special class has excel the scope of Generic Drug User Fee Act (GDUFA) in contrast to traditional small molecular drugs. The recent trends reveal a growing demand that has incentivized pharmaceutical companies to focus more on producing generic versions of complex drugs, such as biosimilars, drug-device combination products, nanotechnological products and controlled-release formulations, topical preparations containing complex drugs, long-acting injectables, and inhalation products. Despite the growth and benefits, the pharmaceutical companies engaged in the production of these products are facing many challenges mainly, advanced analytical techniques to demonstrate bioequivalence and safety, novel complex manufacturing processes to reduce losses, quality issues, regulatory approval, patent litigation, and market competition to bring low-cost products to market. The regulatory status of complex generics varies across different countries. Although the United States Food and Drug Administration (US FDA) has established clear pathways for complex generics by issuing case-by-case product-specific guidelines, other regulatory agencies mainly the European Medical Agency, Health Canada, and (Agencia Nacional de Vigilancia Sanitaria) Brazil are highlighting the challenges associated with the current product-specific guidelines. The regulatory aspect of complex generic is in the nascent stage for countries like India. Harmonization and convergence of regulatory standards are essential for streamlining global access to complex generics. The present review highlights the evolving frontier of complex generics, their classification, trends, regulatory status, and challenges to ensure patient access to safe, effective, and affordable alternative treatments.
Keywords: Complex generics, biologics, drug-device combination, GUDFA, Non-biologics